Istikhdam Uslub Dji Sam Soe (234) fi Qira'ah An-Nushush Ghair Masykulah - Faisal Mubarak Seff; Ridha Darmawaty (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2019)
The superior ability to read Arabic texts without charity is a must for PBA students. But in reality they have difficulty in this because most of the material in the language language they study is rarely used in producing language, especially with the use of various terms that exacerbate these difficulties. Therefore, a strategy that is able to assist them in applying language rules in reading scripts with the use of simple terms and explanations is a must. And the strategy of Dji Sam Soe (234) is one solution with the character of the problem at hand. This study aims to describe the effectiveness of the strategy of Dji Sam Soe (234) in reading texts without a mark on cross-level PBA students in the 2016-2017 academic year by using the Quasi experimental design of one group time series design. Porpusif sampling is a sample selection technique, which is students in the third, fifth and seventh semester who have participated in Qiraatul Kutub supporting courses with instruments in the form of sentences and paragraphs. The results of this study indicate that there is an increase in the ability to read manuscripts without harakat in the form of sentences or paragraphs at each level, although the average ability is slightly different in the ability to read texts in paragraph forms, where seventh semester students are better than semesters three and five.